ازدياد ظاهرة الطلاق في زنجبار أسبابها وآثارها وعلاجها: دراسة مقاصدية تحليلية - رمضان، بلال جمعة (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research has investigated the major reasons of increasing phenomenon of divorce in Zanzibar and identified its impacts, putting forth some suggestions for tackling this issue. The problem statement of this research is rapid growth of divorce rate in Zanzibar and its consequences on society and morality. This fact demands serious study and scientific research to scrutinize the causes and effects of divorces and to propose solutions for this problem from maqaṣid al-shari'ah perspective. For this study, the researcher has adopted descriptive method, analytical method and personal interviews, more than eighty interviews were conducted with interested people who are aware of this phenomenon. This study has produced several findings and major findings are as follows. The main reasons for increasing phenomenon of divorce in Zanzibar are wrong selection of partner, interference of family members, forced marriage, financial incapacity, alcoholism, affiliation to various political parties, tribal chauvinism. The rising rate of divorce has left several consequences on couples and their children through various aspects including social, psychological and moral. This phenomenon has resulted in spread of adultery and street children in Zanzibar societies. This issued could be solved by selection of a good partner, kind treatment among couple, premarital training for soon-to-be married couples, religious awareness, reconciliation and implementation of maqaṣid of divorce, khul' (divorce instigated by the wife), 'iddah (waiting Period for a widow), marital rights and premarital procedures.